2011
DOI: 10.1084/jem.20102101
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CXCR3 facilitates CD8+ T cell differentiation into short-lived effector cells leading to memory degeneration

Abstract: CXCR3 regulates CD8+ T cell recruitment to sites of inflammation, thus dictating CD8+ T cell contraction and subsequent effector/memory cell fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
181
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(198 citation statements)
references
References 80 publications
(138 reference statements)
16
181
1
Order By: Relevance
“…We now add that CXCL10 performs such a function for CD8 + T cells, in accordance with a recent finding that CXCL10 produced by DCs can support the generation of a CD8 + T cell response (50). Interestingly, recent findings on the role of CXCR3 in fate determination of primed CD8 + T cells further support this notion (51,52). CXCR3 binds CXCL9, CXCL10, and CXCL11, but C57BL/6 mice only express CXCL9 and CXCL10 (52).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We now add that CXCL10 performs such a function for CD8 + T cells, in accordance with a recent finding that CXCL10 produced by DCs can support the generation of a CD8 + T cell response (50). Interestingly, recent findings on the role of CXCR3 in fate determination of primed CD8 + T cells further support this notion (51,52). CXCR3 binds CXCL9, CXCL10, and CXCL11, but C57BL/6 mice only express CXCL9 and CXCL10 (52).…”
Section: Discussionsupporting
confidence: 90%
“…This redistribution was impaired when the CD8 + T cells lacked expression of CXCR3. It was suggested that this redistribution within the priming organ and the consequent longer or shorter contact with Ag-presenting DCs determined the long-term fate of the CD8 + T cells (51,52). Our data are in full agreement with the concept that CXCR3 and CXCL10 play a role in the localization of primed CD8 + T cells at the site of priming and, thereby, affect the CD8 + T cell response.…”
Section: Discussionsupporting
confidence: 89%
“…(9,10) In particular, recent studies have shown that CXCR3 chemokine receptors are involved in promoting CD8 + T cell commitment to an effector fate rather than a memory fate. (11,12) The reaction was then developed with 100 μL of TMB liquid substrate solution (T4444, Sigma) at room temperature for 30 min in the dark and stopped by the addition of 1 M sulfuric acid. The absorbance at 450 nm was measured by an ELISA plate reader (Tecan Sunrise).…”
Section: Construction Of Np Expression Vector and Expression And Purimentioning
confidence: 99%
“…For in vivo memory generation, B6 mice were adoptively transferred with CD8 + T cells (1 3 10 4 ) from CD45.1 Rag2 KO OT-I mice and infected with PbA-OVA or LM-OVA (18). Postinfection with PbA-OVA, mice were treated with chloroquine and sulfadiadne (Sigma-Aldrich) for 2 wk between days 6 (parasitemia 2.1-12.1%) and 20 as described previously with slight modification (19).…”
Section: Generation Of Memory Cellsmentioning
confidence: 99%